Sodium ion layered oxide positive electrode material inhibiting transition metal layer slip and preparation method thereof
By pervalent ion doping the sodium ion layered oxide positive electrode material, the performance attenuation problem caused by transition metal layer slip is solved, and the cyclic stability and rate performance of the material are significantly improved.
Patent Information
- Application Number
- CN202310306297.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-03-27
AI Technical Summary
The layered metal oxide positive electrode materials of existing sodium ion batteries are prone to transition metal layer slippage at the end of charging, resulting in the accumulation of structural defects, rapid attenuation of capacity and voltage, poor rate performance and short cycle life.
By doping the transition metal layer, oxygen layer and sodium layer of the sodium layer of the sodium ion layered oxide positive electrode material, metal ions with larger ion radius, smaller Li+ ions and F-ions are introduced to suppress slippage of the transition metal layer.
It effectively suppresses the transition metal layer slip of the cathode material during the electrochemical cycle, improves the cycle stability and rate performance, and extends the service life of the battery.
Smart Images

Figure CN116425215B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion battery technology and battery materials, and specifically relates to a sodium ion layered oxide positive electrode material capable of inhibiting the slippage of a transition metal layer and a preparation method thereof. Background Art
[0002] The rapid development of electrochemical energy storage technology has facilitated people's daily mobile life. Today, lithium-ion batteries are widely used in many portable electronic devices, such as smart phones, handheld tools, laptops, digital cameras, etc. However, the recent explosive growth of new energy vehicles and static energy storage industries has led to a large consumption of lithium resources, and the uneven distribution of lithium mines around the world has restricted the mining of lithium salts, which has led to the continuous rise in the price of battery-grade lithium salts, thereby limiting the application of lithium-ion batteries in large-scale energy storage equipment such as smart grids and energy storage base stations.
[0003] Sodium and lithium are adjacent elements of the same main group with many similar physical and chemical properties. Unlike lithium, sodium is the alkali metal element with the highest natural abundance in the earth's crust and sodium resources are widely distributed around the world. Therefore, sodium-ion batteries are considered to be a highly cost-effective secondary battery energy storage system that can replace or complement lithium-ion batteries in some large-scale energy storage devices. In addition, the similar manufacturing process of sodium-ion batteries and lithium-ion batteries is conducive to the modification of existing battery production lines and equipment, realizing the rapid commercialization of sodium-ion batteries.
[0004] However, due to the poor electrochemical performance of the positive electrode materials of sodium-ion batteries, their electrochemical performance is still far behind that of lithium-ion batteries. The positive electrode materials of sodium-ion batteries currently mainly include layered metal oxides, polyanionic materials, Prussian blue and its analogs. Among them, layered metal oxides have the characteristics of high theoretical specific capacity, simple preparation, and cheap raw materials, and are considered to be the material system with the most commercial prospects. At present, layered metal oxides still have problems such as low actual capacity, low voltage platform, short cycle life, and poor rate performance. In particular, during the electrochemical cycle, the interlayer spacing of the transition metal layer of the positive electrode material will continue to expand as the sodium ions are released, eventually leading to the slip of the transition metal layer at the end of the charge, causing phase structure changes, so that structural defects continue to accumulate in the electrode and produce large volume changes, and ultimately leading to the rapid decay of the capacity and voltage of the sodium-ion battery. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a sodium ion layered metal oxide positive electrode material and a preparation method thereof that inhibits transition metal layer slip. The present invention simultaneously performs heterovalent ion doping on the transition metal layer, oxygen layer and sodium layer of the sodium ion layered metal oxide, which can effectively inhibit the transition metal layer slip phenomenon of the existing sodium ion battery layered oxide at the end of charging, and overcome the problems of poor rate performance and short cycle life of the layered metal oxide positive electrode in the sodium ion battery.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] The technical solution of the present invention is as follows:
[0008] The sodium ion layered oxide positive electrode material for inhibiting transition metal layer slip of the present invention is a P2 type layered metal oxide positive electrode material, and its crystal structure space group is P63 / mmc. The structural chemical formula of the sodium ion layered oxide positive electrode material is Na x A a Li b Ni c Mn 0.67 O 2-y F y , where 0.55≤x≤0.83, 0.01≤a≤0.2, 0.01≤b≤0.27, 0≤c<0.33, 0.05≤y≤0.15, x+a<0.85, b+c=0.33; ion A is Mg 2+ , K + 、Ag + , Ca 2+ At least one of the above is in the sodium layer; Li + The ions are in the transition metal layer; F - The ions are in the oxygen layer.
[0009] Preferably, in the chemical formula, 0.61≤x≤0.8, 0.03≤a≤0.1, 0.01≤b≤0.15, and 0.23≤c<0.33.
[0010] Preferably, the particle size of the sodium ion layered oxide positive electrode material is 500nm to 5μm. If the particle size is too small, the specific surface area of the material will increase significantly, thereby causing serious interface side reactions; if the particle size is too large, the Na + The transmission path inside the material is too long, which causes the electrochemical performance of the material to deteriorate.
[0011] The invention discloses an application of a sodium ion layered oxide positive electrode material in a sodium ion battery.
[0012] The present invention provides a method for preparing a sodium ion layered metal oxide positive electrode material, which specifically comprises the following steps:
[0013] (1) According to the structural chemical formula, raw materials that meet the stoichiometric ratio of the chemical formula are ball-milled and mixed uniformly, wherein the sodium source includes at least one of sodium carbonate, sodium acetate, sodium oxide, and sodium nitrate; the source of A ions is at least one of potassium carbonate, potassium acetate, potassium oxide, potassium nitrate, calcium nitrate, calcium carbonate, calcium oxide, silver nitrate, silver oxide, magnesium acetate, and magnesium oxide; the lithium source is at least one of lithium carbonate, lithium acetate, lithium oxide, and lithium nitrate; the nickel source is at least one of nickel acetate and nickel oxide; the manganese source is at least one of manganese acetate and manganese oxide; the fluorine source is at least one of lithium fluoride and sodium fluoride;
[0014] Step 2: applying a pressure of 1 to 20 MPa to the mixed raw materials to obtain a dense disc, and the tableting time is 1 second to 30 minutes;
[0015] Step 3: Sinter the dense disc at high temperature and then cool it to room temperature to obtain a layered metal oxide positive electrode material. The sintering temperature is 700°C to 1200°C, the sintering time is 6h to 24h, and the heating and cooling rate is 1°C / min to 10°C / min.
[0016] Preferably, in step (1), the sodium source and the lithium source are carbonate or acetate; when the source of A ions is potassium, the potassium source is carbonate or acetate. Nitrates will undergo a violent decomposition reaction during high temperature calcination.
[0017] Preferably, in step 2, the pressure is 5-10 MPa, and the tableting time is preferably 5-15 min. Too low a pressure or too short a tableting time will result in too small a particle size of the obtained material, resulting in a decrease in electrochemical performance; too high a pressure or too long a tableting time will result in too large a particle size of the obtained material, resulting in a decrease in electrochemical performance.
[0018] Preferably, in step 3, the sintering temperature is 800°C to 1000°C, and the sintering time is 10h to 20h. When the sintering temperature is higher than 1000°C and the sintering time is greater than 20h, the material will undergo oxygen depletion reaction, resulting in material structural defects; when the temperature is lower than 800°C and the sintering time is lower than 10h, the material will not be sufficiently embedded in sodium, resulting in a decrease in electrochemical performance.
[0019] Preferably, in step 3, the material sintering process is carried out in oxygen, air, nitrogen or argon. Sintering in hydrogen will result in oxygen ion vacancies in the bulk phase of the material, resulting in a decrease in electrochemical performance.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention introduces metal ions with larger ionic radius into the sodium layer of the layered metal oxide material and introduces Li ions with smaller ionic radius into the transition metal layer. + F is introduced into the ion and oxygen layer- Ions are used to inhibit the continuous expansion of the transition metal layer spacing in the positive electrode material during the electrochemical cycle, which eventually causes the transition metal layer to slip. Among them, the introduction of metal ions with larger ionic radius into the sodium layer can play a supporting role in the sodium layer, increase the cation content in the sodium layer at the end of charging and hinder the orderly arrangement of sodium ions and vacancies; the introduction of Li into the transition metal layer + Partially replaced Ni 2+ , this method uses Li + The reversible migration between the transition metal layer and the sodium layer can occur during the charge and discharge process, which reduces the electrostatic repulsion between the transition metal layers at the end of charging and inhibits the expansion of the sodium layer spacing. - Ions are to partially replace O 2- , thereby reducing the electrostatic repulsion between transition metal layers and increasing the reversibility of oxygen reaction at the end of charging. Therefore, the simultaneous introduction of multiple heterovalent ions at different metal ion sites in the material can effectively inhibit the structural phase transition that occurs at high voltage, reduce the volume change of the material, stabilize the two-dimensional structural framework of the material, and significantly improve the cycle stability and rate performance of the layered metal oxide positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 for Na 0.61 Ca 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 SEM image of the material.
[0023] Figure 2 The figure is a comparison chart of the electrochemical cycle performance of using Example 4 and Comparative Examples 1, 2, 3, and 4 as positive electrode materials in sodium ion batteries.
[0024] Figure 3 This is a comparison chart of the rate performance of using Example 4 and Comparative Examples 1, 2, 3, and 4 as positive electrode materials in sodium ion batteries. DETAILED DESCRIPTION
[0025] The technical scheme of the present invention is further illustrated and described according to the following specific examples. However, the following examples and comparative examples are only used to illustrate and explain the present invention and are not used to limit the present invention.
[0026] Example 1
[0027] (1) Weigh 0.917 g Na2CO3, 0.0649 g NaF, 0.3648 g Ca(NO3)2·4H2O, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0028] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h at a heating rate of 5 °C / min. After cooling to room temperature, Na 0.61 Ca 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 500nm to 5μm and a morphology such as Figure 1 shown.
[0029] (3) 1 g of positive electrode material was mixed with 0.125 g of PVDF binder and 0.125 g of acetylene black, and 0.5 mL of NMP solvent was added. The mixture was mixed in a degassing machine at 1200 rpm for 10 min to obtain positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil using a scraper, and then the aluminum foil was transferred to an 80°C vacuum oven and dried for 12 h. The dried positive electrode slurry was cut into discs with a diameter of 14 mm on a cutting machine.
[0030] (4) The disc prepared in step (3) was used as the positive electrode, a sodium metal disc with a diameter of 14 mm and a thickness of 0.2 mm was used as the negative electrode, a glass fiber with a diameter of 19 mm and a thickness of 1 mm was used as the separator, and a 1M NaClO4 PC solution was used as the electrolyte to assemble a button cell in a CR2016 battery case.
[0031] (5) Figure 2 As shown, the button cell assembled in step (4) is first charged at 16 mA g -1 After 2 cycles of activation at a current density of 160 mA g -1 The current density of the material was used for the cycle performance test, and the first cycle capacity of the material was 125 mAh g -1 The discharge capacity retention rate after 200 cycles is 83.8%.
[0032] (6) Figure 3 As shown, the button cell assembled in step (4) is charged at 16 mA g -1 , 160mA g -1, 480mA g -1 , 800mA g -1 , 1600mA g -1 The rate performance test was carried out under the gradient current density of 154 mAh g -1 , 134mAh g -1 , 109mAh g -1 , 98mAh g -1 , 77mAh g -1 .
[0033] Example 2
[0034] (1) Weigh 1.1288 g Na2CO3, 0.0695 g Ag2O, 0.0649 g NaF, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80 °C and dry it for 1 h.
[0035] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h. After cooling to room temperature, Na 0.69 Ag 0.02 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 700nm to 4.2μm.
[0036] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 1.
[0037] Example 3
[0038] (1) Weigh 1.1124 g Na2CO3, 0.0649 g NaF, 0.064 g K2CO3, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0039] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h. After cooling to room temperature, Na 0.68 K 0.03 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 700nm to 3μm.
[0040] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 1.
[0041] Example 4
[0042] (1) Weigh 0.917 g Na2CO3, 0.0649 g NaF, 0.06 g MgO, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0043] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h. After cooling to room temperature, Na 0.61 Mg 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 500nm to 4.8μm.
[0044] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 1.
[0045] Table 1 Electrochemical performance of button cells assembled in Examples 1 to 4
[0046] Material <![CDATA[Current density (mA g -1 )]]> Voltage range (V) <![CDATA[Initial capacity (mAg h -1 )]]> 200 cycles capacity retention rate Example 1 160 1.5~4.3 125 83.8% Example 2 160 1.5~4.3 131 81.9% Example 3 160 1.5~4.3 123 80.1% Example 4 160 1.5~4.3 118 82.6%
[0047] Example 5
[0048] (1) Weigh 0.6545 g Na2CO3, 0.1947 g NaF, 0.4146 g K2CO3, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80 °C and dry it for 1 h.
[0049] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 1 MPa was applied on a hydraulic press and maintained for 30 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 1200°C for 20 h at a heating and cooling rate of 3°C / min. After cooling to room temperature, Na 0.55 K 0.2 Li 0.1 Ni 0.23 Mn 0.67 O 1.85 F 0.15 The material has a particle size of 7.2μm to 10μm.
[0050] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 2.
[0051] Example 6
[0052] (1) Weigh 1.2762 g of Na2CO3, 0.0649 g of NaF, 0.0730 g of Ca(NO3)2·4H2O, 0.2382 g of Li2CO3, 0.112 g of NiO, and 1.7475 g of MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0053] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 20 MPa was applied on a hydraulic press and maintained for 1 second to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 700°C for 6 hours at a heating and cooling rate of 1°C / min. After cooling to room temperature, Na 0.83 Ca 0.01 Li 0.27 Ni 0.05 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 100nm to 3μm.
[0054] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 2.
[0055] Example 7
[0056] (1) Weigh 0.8737 g Na2CO3, 0.0649 g NaF, 0.3648 g Ca(NO3)2·4H2O, 0.0088 g Li2CO3, 0.717 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0057] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 20 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 1000°C for 10 h at a heating rate of 10°C / min. After cooling to room temperature, Na 0.6 Ca 0.05 Li 0.01 Ni 0.32 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 1 μm to 5.5 μm.
[0058] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 2.
[0059] Table 2 Electrochemical performance of button cells assembled in Examples 3 to 7
[0060] Material <![CDATA[Current density (mA g -1 )]]> Voltage range(V) <![CDATA[Initial capacity (mAg h -1 )]]> 200 cycles capacity retention rate Example 5 160 1.5~4.3 122 80.7% Example 6 160 1.5~4.3 110 81.8% Example 7 160 1.5~4.3 131 79.6%
[0061] The following examples are Na obtained in different sintering atmospheres. 0.61 Ca 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 Material:
[0062] Example 8
[0063] (1) Weigh 0.917 g Na2CO3, 0.0649 g NaF, 0.3648 g Ca(NO3)2·4H2O, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0064] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a tube furnace for sintering at 900 °C for 15 h. The sintering atmosphere was air and the heating and cooling rate was 5 °C / min. After cooling to room temperature, Na 0.61 Ca 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 500nm to 5μm.
[0065] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 3.
[0066] Example 9
[0067] (1) Weigh 0.917 g Na2CO3, 0.0649 g NaF, 0.3648 g Ca(NO3)2·4H2O, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0068] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a tube furnace for sintering at 900 °C for 15 h. The sintering atmosphere was oxygen and the heating and cooling rate was 5 °C / min. After cooling to room temperature, Na 0.61 Ca 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 900nm to 5.4μm.
[0069] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 3.
[0070] Example 10
[0071] (1) Weigh 0.917 g Na2CO3, 0.0649 g NaF, 0.3648 g Ca(NO3)2·4H2O, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0072] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a tube furnace for sintering at 900 °C for 15 h. The sintering atmosphere was nitrogen and the heating and cooling rate was 5 °C / min. After cooling to room temperature, Na 0.61 Ca 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 300nm to 3.6μm.
[0073] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 3.
[0074] Embodiment 11
[0075] (1) Weigh 0.917 g Na2CO3, 0.0649 g NaF, 0.3648 g Ca(NO3)2·4H2O, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80°C and dry it for 1 h.
[0076] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a tube furnace for sintering at 900 °C for 15 h. The sintering atmosphere was argon and the heating and cooling rate was 5 °C / min. After cooling to room temperature, Na 0.61 Ca 0.05 Li 0.1 Ni 0.23 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 300nm to 3.2μm.
[0077] Using the same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1, the electrochemical performance of the button cell assembled in this example can be obtained as shown in Table 3.
[0078] Table 3 Electrochemical performance of button cells assembled in Examples 8 to 11
[0079]
[0080]
[0081] Comparative Example 1
[0082] Synthesis of Na2O3 without heterovalent metal ion doping 0.67 Ni 0.33 Mn 0.67 O2 material.
[0083] (1) Weigh 1.0971 g Na2CO3, 0.7394 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80 °C and dry it for 1 h.
[0084] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h at a heating rate of 5 °C / min. After cooling to room temperature, Na 0.67 Ni 0.33 Mn 0.67 O2 material, the particle size of which is 600nm~5.5μm.
[0085] The same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1 were used. Figure 2 and Figure 3 As shown in FIG. 1 , the first cycle capacity of the button cell assembled in this comparative example is 149 mAg h -1 The discharge capacity retention rate after 200 cycles was 9.5%, and at 16 mA g -1 , 160mA g -1 , 480mA g -1 , 800mA g -1 , 1600mA g -1 The discharge capacity at the current density of 180 mA g h -1 102mAg h -1 , 75mAg h -1 、66mAg h -1 , 52mAg h-1 .
[0086] Comparative Example 2
[0087] Synthesis of single ion-doped Na 0.57 Ca 0.05 Ni 0.33 Mn 0.67 O2 material.
[0088] (1) Weigh 0.9333 g Na2CO3, 0.3648 g Ca(NO3)2·4H2O, 0.7394 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h, then place in an oven at 80 °C to dry for 1 h;
[0089] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h at a heating rate of 5 °C / min. After cooling to room temperature, Na 0.57 Ca 0.05 Ni 0.33 Mn 0.67 O2 material, the particle size is 550nm~4μm.
[0090] The same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1 were used. Figure 2 and Figure 3 As shown in FIG. 1 , the first cycle capacity of the button cell assembled in this comparative example is 120 mA g h -1 The discharge capacity retention rate after 200 cycles was 65.5%, and at 16 mA g -1 , 160mA g -1 , 480mA g -1 , 800mA g -1 , 1600mA g -1 The discharge capacity at the current density of 166 mA g h -1 , 117mAg h -1 、81mAg h -1 , 72mAg h -1 、63mAg h -1 .
[0091] Comparative Example 3
[0092] Synthesis of single ion-doped Na 0.76 Li 0.1 Ni 0.23 Mn 0.67O2 material.
[0093] (1) Weigh 1.2444 g Na2CO3, 0.1141 g Li2CO3, 0.5153 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80 °C and dry it for 1 h.
[0094] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h at a heating rate of 5 °C / min. After cooling to room temperature, Na 0.76 Li 0.1 Ni 0.23 Mn 0.67 O2 material, the particle size of which is 450nm~4.3μm.
[0095] The same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1 were used. Figure 2 and Figure 3 As shown in FIG. 1 , the first cycle capacity of the button cell assembled in this comparative example is 124 mAg h -1 The discharge capacity retention rate after 200 cycles was 22.6%, and at 16 mA g -1 , 160mA g -1 , 480mA g -1 , 800mA g -1 , 1600mA g -1 The discharge capacity at the current density of 142 mA g h -1 、119mAg h -1 , 103mAg h -1 、95mAg h -1 、81mAg h -1 .
[0096] Comparative Example 4
[0097] Synthesis of single ion-doped Na 0.61 Ni 0.33 Mn 0.67 O 1.95 F 0.05 Material.
[0098] (1) Weigh 0.917 g Na2CO3, 0.0649 g NaF, 0.7394 g NiO, and 1.7475 g MnO2 into a ball mill tube, add ball mill beads and acetone, and mill the mixture at 300 rpm for 5 h. Then, place the mixture in an oven at 80 °C and dry it for 1 h.
[0099] (2) The mixed powder was transferred to a tablet pressing mold, and a pressure of 10 MPa was applied on a hydraulic press and maintained for 5 min to obtain a dense disc. The disc was then placed in an alumina crucible and placed in a muffle furnace for sintering at 900 °C for 15 h at a heating rate of 5 °C / min. After cooling to room temperature, Na 0.61 Ni 0.33 Mn 0.67 O 1.95 F 0.05 The material has a particle size of 400nm to 6μm.
[0100] The same electrode preparation, battery assembly and electrochemical performance testing scheme as in Example 1 were used. Figure 2 and Figure 3 As shown in FIG. 1 , the first cycle capacity of the button cell assembled in this comparative example is 148 mAg h -1 The discharge capacity retention rate after 200 cycles was 17.5%, and at 16 mA g -1 , 160mA g -1 , 480mA g -1 , 800mA g -1 , 1600mA g -1 The discharge capacity at the current density of 185 mA g h -1 、95mAg h -1 、67mAg h -1 , 55mAg h -1 , 40mAg h -1 .
[0101] Table 4 Electrochemical performance of button cells assembled in Comparative Examples 1 to 4
[0102] Material <![CDATA[Current density (mA g -1 )]]> Voltage range(V) <![CDATA[Initial capacity (mAg h -1 )]]> 200 cycles capacity retention rate Comparative Example 1 160 1.5~4.3 149 9.5% Comparative Example 2 160 1.5~4.3 120 65.5% Comparative Example 3 160 1.5~4.3 124 22.6% Comparative Example 4 160 1.5~4.3 148 17.5%
[0103] By comparing the electrochemical performance tables of the button cells of the embodiment with those of the four comparative examples, it can be seen that the 200-cycle capacity retention rate obtained in the embodiment is much greater than that of each comparative example, thereby proving that the positive electrode material obtained by the method of the present invention significantly improves the cycle stability and rate performance of the metal oxide positive electrode.
Claims
1. A sodium ion layered oxide positive electrode material that inhibits transition metal layer slip, characterized in that: The structural chemical formula of the sodium ion layered oxide material is Na x A a Li b Ni c Mn 0.67 O 2-y F y , where 0.55≤x≤0.83, 0.01≤a≤0.2, 0.01≤b≤0.27, 0≤c<0.33, 0.05≤y≤0.15, x+a<0.85, b+c=0.33; ion A is Mg 2+ , K + 、Ag + , Ca 2+ At least one of the above is in the sodium layer; Li + The ions are in the transition metal layer; F - The ions are in the oxygen layer.
2. The sodium ion layered oxide positive electrode material for inhibiting transition metal layer slip according to claim 1, characterized in that: 0.61≤x≤0.8, 0.03≤a≤0.1, 0.01≤b≤0.15, 0.23≤c<0.
33.
3. The sodium ion layered oxide positive electrode material for inhibiting transition metal layer slip according to claim 1, characterized in that: The particle size of sodium ion layered oxide positive electrode materials is 100 nm ~ 10 μm.
4. The sodium ion layered oxide positive electrode material for inhibiting transition metal layer slip according to claim 3, characterized in that: The particle size of sodium ion layered oxide positive electrode materials is 500 nm ~ 5 μm.
5. Use of the sodium ion layered oxide positive electrode material according to any one of claims 1 to 4 in a sodium ion battery.
6. A method for preparing the sodium ion layered oxide positive electrode material according to any one of claims 1 to 4, characterized in that: The method comprises the following synthesis steps: Step 1: ball-milling and mixing the raw materials that meet the stoichiometric ratio uniformly, wherein the sodium source includes at least one of sodium carbonate, sodium acetate, sodium oxide, and sodium nitrate; the source of A ions is at least one of potassium carbonate, potassium acetate, potassium oxide, potassium nitrate, calcium nitrate, calcium carbonate, calcium oxide, silver nitrate, silver oxide, magnesium acetate, and magnesium oxide; the lithium source is at least one of lithium carbonate, lithium acetate, lithium oxide, and lithium nitrate; the nickel source is at least one of nickel acetate and nickel oxide; the manganese source is at least one of manganese acetate and manganese oxide; the fluorine source is at least one of lithium fluoride and sodium fluoride; Step 2: applying a pressure of 1 to 20 MPa to the mixed raw materials to obtain a dense disc, and the tableting time is 1 s to 30 min; Step 3: Sinter the dense disc at high temperature and then cool it to room temperature to obtain a layered metal oxide positive electrode material. The sintering temperature is 700ºC ~ 1200ºC, the sintering time is 6 h ~ 24 h, and the heating and cooling rate is 1ºC / min ~ 10ºC / min.
7. The method for preparing the sodium ion layered oxide positive electrode material according to claim 6, characterized in that: In step 1, the sodium source and the lithium source are carbonate or acetate; when the source of A ions is potassium, the potassium source is carbonate or acetate.
8. The method for preparing the sodium ion layered oxide positive electrode material according to claim 6, characterized in that: In step 2, the tableting pressure is 5 to 10 MPa, and the tableting time is 5 to 15 min.
9. The method for preparing the sodium ion layered oxide positive electrode material according to claim 6, characterized in that: In step three, the sintering temperature is 800ºC ~1000ºC, and the sintering time is 10 h ~20 h.
10. The method for preparing the sodium ion layered oxide positive electrode material according to claim 6, characterized in that: In step three, the material sintering process is carried out in oxygen, air, nitrogen or argon.
Citation Information
Patent Citations
Layered oxide positive electrode, preparation method and application thereof and sodium-ion battery containing layered oxide positive electrode
CN111564605A
High-voltage sodium ion battery layered oxide positive electrode material
CN113764669A